Tower as magnetic antipinning core in a small superconducting sample - Barba-Ortega, J.; Joya, Miryam R.; Sardella, Edson [UNESP] (Elsevier B.V., 2014)
Using the nonlinear Ginzburg-Landau equations we study the vortex configurations in a superconducting square with a central square pillar in the presence of a uniform applied magnetic field. The presence of the pillar changes the vortex structure in the superconducting sample considerably. We calculate magnetization, magnetic induction, supercurrent and vorticity, which show different vortex configurations as a function of magnetic field. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Vortex; Ginzburg-Landau; Mesoscopic; Pillars